Essays on voting behaviour. A historical perspective - Lehmann, Sibylle H. (Trinity College (Dublin, Ireland). Department of Economics, 2008)
The present thesis consists of two parts. The first part contains two essays that study voting behaviour in general elections that took place before turning points in trade policy. They aim to shed light on why European countries pursued different trade policies at the end of the 19th century, although often the structure of the societies were quite similar and therefore the preferred trade policies should have been similar as well.
Keywords: Economics, Ph.D.; Ph.D. Trinity College Dublin